Construction method and application of real‐time monitoring and early‐warning model for anaerobic reactor leakage. Issue 4 (22nd February 2020) - Wang, Feng; Deng, Fujie; Wang, Yipeng
Abstract: The anaerobic reactor is one of the most critical reaction devices for biogas engineering, wherein is usually a large amount of flammable gas methane. Fire and explosion accidents will be easily triggered if the gas leaks, threatening the surrounding buildings, equipment, personnel, and so forth. Avoiding the significant accidents caused by CH4 leakage has become a critical issue in the design and condition monitoring for an anaerobic reactor. This article presents a model construction method for leakage early‐warning. Incident database and hazard and operability analysis (HAZOP) can be utilized to identify the leakage risks, and computational fluid dynamics (CFD) simulation and consequence quantity calculation can be used to determine the consequence influence ranges. The calculation results can be employed to establish prediction models for abnormal situations. Process safety management (PSM) data and risk analysis results can be combined with the possible abnormal situations to assist operators in adopting the right solutions. An early‐warning system has been developed to illustrate the industrial application of the model. It can be concluded that collecting multi‐parameter values according to the real‐time changes in the actual production process, continuous monitoring and early‐warning of leakage risk, and so forth, will contribute to accident avoiding and emergency response in reactor operations.